1998
DOI: 10.1212/wnl.51.4.1051
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic changes in sleep apnea syndrome and effect of continuous positive airway pressure treatment

Abstract: These findings suggest an association between OSAS and diminished cerebral vasodilator reserve. This condition may be related to the increased susceptibility to cerebral ischemia in patients with OSAS, particularly evident in the early morning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
1
20

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 13 publications
8
86
1
20
Order By: Relevance
“…In contrast, over the same time period, morning hypercapnic cerebral vascular reactivity is markedly reduced, a finding that is in agreement with others. 1,16 The similarity in the magnitude of the hypoxic cerebral vascular response between the evening and morning is noteworthy, because we have previously reported that this response is absent during NREM sleep 7 ; indeed, hypoxia is associated with a reduction in CBF during NREM sleep. 7 Although the mechanism responsible for the abolition of this response is unknown, the present data would suggest that, in the majority of individuals, the return of the hypoxic response on waking occurs rapidly.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In contrast, over the same time period, morning hypercapnic cerebral vascular reactivity is markedly reduced, a finding that is in agreement with others. 1,16 The similarity in the magnitude of the hypoxic cerebral vascular response between the evening and morning is noteworthy, because we have previously reported that this response is absent during NREM sleep 7 ; indeed, hypoxia is associated with a reduction in CBF during NREM sleep. 7 Although the mechanism responsible for the abolition of this response is unknown, the present data would suggest that, in the majority of individuals, the return of the hypoxic response on waking occurs rapidly.…”
Section: Discussionmentioning
confidence: 74%
“…16,18 -20 The relative state of hypercapnia associated with sleep could, therefore, lead to a downregulation of CO 2 or pH receptors and an impaired morning cerebral vascular response to CO 2 . 16 This is the first study to simultaneously measure changes in NO and cerebral vascular reactivity. Total nitriteϩnitrate levels trended toward a decrease from evening to morning; a similar trend was reported by Elherick et al 10 However, the lack of correlation between total nitriteϩnitrate levels and hypercapnic cerebral vascular reactivity suggests that changes in total nitriteϩnitrate levels from evening to morning do not explain the fall in hypercapnic cerebral vascular reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, nCPAP is the treatment of choice to improve several internal parameters in patients with OSA. [14][15][16][17][18] Vitamin D has pleiotropic effects and plays major roles in an extended range of organ functions and disorders. 7 Vitamin D is a fat-soluble secosteroid hormone which undergoes two hydroxylation reactions, first in the liver and second in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Age predisposes to SDB (Fleury 1992). SDB is recognized as an important risk factor for neurovascular disease (Diomedi et al 1998;Mayer et al 1999;Kotterba et al 1998).…”
Section: P Rimarymentioning
confidence: 99%